092 Promotion of para athlete well-being in South Africa (the PROPEL studies), part I: profiles and prevalence of psychological distress. (3rd March 2020) - Badenhorst, Marelise; Runciman, Phoebe; Brown, James Craig; Derman, Wayne
Abstract : Background: There is a paucity of research investigating the mental health profiles of para athletes globally, especially in South Africa. Objective: To describe the mental health profiles of a representative sample of para athletes in South Africa. Design: Descriptive, cross-sectional survey. Setting: National to international level athletes competing in the 2019 National Championships for athletes with impairments. Patients (or Participants): A total of 124 athletes (93 males; 31 females) with a mean age 26.7 (±9.2). Interventions (or assessment of risk factors): Between-group differences were analysed using the Mann-Whitney U test or one-way ANOVA. On completion of the questionnaires, all athletes were given information about mental health support services. Main outcome measurements: Mental health was measured with the Trait component of the State/Trait Anxiety Inventory (STAI) and the Kessler Psychological Distress Scale (K-10). Results: The mean score for the STAI was 39.2 (±9.3) units. A quarter (25%) of all athletes scored 45 and above, in line with scores of patients with a psychological/psychiatric diagnosis. On average, females (35.9±8.7) had better STAI scores than males (40.3±9.3; p =0.02) and married (32.6±8.9) athletes had better scores than single (40.2±8.9; p =0.002) athletes. The mean K-10 questionnaire score was 20.4 (±6.4) units, with no gender difference. However, K-10 scores were significantly higher in single than in married athletes ( U =415.5; p =0.002). Using a cut-off score of ≥28 and ≥16 on the K-10, 12.2% and 76.4% of athletes had symptoms of distress, respectively. Neither scale was associated with level of competition, sport code or impairment type. The K-10 and STAI scores were highly correlated (rs =0.64, p<0.001). Conclusions: The study found high rates of psychological distress among para athletes, which is an important first step towards the development of prevention strategies. There is a need to further understand and identify mechanisms affecting mental health in this population.